Reciprocal relations between autonomous motivation from self-determination theory and social cognition constructs from the theory of planned behavior: A cross-lagged panel design in sport injury prevention. (May 2020) - Chan, Derwin King Chung; Zhang, Lei; Lee, Alfred Sing Yeung; Hagger, Martin S.
Abstract: Objectives: The present study examined reciprocal relations between autonomous motivation from self-determination theory (SDT) and constructs from the theory of planned behavior (TPB) in a sport injury context. Methods: The study adopted a three-wave longitudinal cross-lagged panel design. Physical education students in China ( N = 4414; M age = 14.42, SD = 1.75) completed self-report measures of autonomous motivation, attitude, subjective norm, and perceived behavioral control with respect to sport injury prevention at baseline (T1) and at two follow-up occasions one (T2) and three (T3) months later. Proposed reciprocal relations between autonomous motivation and the TPB constructs controlling for construct stability over time were tested using structural equation modeling. Results: Three cross-lagged SEMs for effects of constructs measured at T1 on constructs measured at T2 and T3, and effects of constructs measured at T2 on constructs measured at T3 met goodness-of-fit criteria (CFI > 0.95, TLI > 0.94, RMSEA = 0.03, SRMR = 0.05) with consistent patterns of effects. Across the three models, autonomous motivation predicted the prospectively-measured TPB constructs with small-to-medium effect sizes (β range = 0.17 to 0.32, ps < .001), but associations between the TPB variables and prospectively-measured autonomous motivation were markedly smaller in size (β range = 0.01 to 0.18, ps range = .001 to .892). Conclusions: Findings provide initial support for the temporal ordering of the constructs in the integrated model of SDT and TPB in a sport injury context. Autonomous motivation from SDT is likely to be an antecedent of the constructs from the TPB. Highlights: Reciprocal effects of autonomous motivation and beliefs about future behavior were tested in a cross-lagged panel design. Autonomous motive is likely to be the antecedent of positive beliefs toward sport injury prevention behaviors. Findings provide formative research on potentially modifiable targets for sport injury prevention behavioral interventions. Future intervention research targeting change in autonomous motivation and examining effects on beliefs is needed.